2008
DOI: 10.1073/pnas.0810698105
|View full text |Cite
|
Sign up to set email alerts
|

nemy encodes a cytochrome b561 that is required for Drosophila learning and memory

Abstract: Although many genes have been shown to play essential roles in learning and memory, the precise molecular and cellular mechanisms underlying these processes remain to be fully elucidated. Here, we present the molecular and behavioral characterization of the Drosophila memory mutant nemy. We provide multiple lines of evidence to show that nemy arises from a mutation in a Drosophila homologue of cytochrome B561. nemy is predominantly expressed in neuroendocrine neurons in the larval brain, and in mushroom bodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
(26 reference statements)
1
33
0
Order By: Relevance
“…It is possible that compensatory changes in the prt mutant mitigate its effect on learning. Alternatively, the release of a peptide, rather than a classical neurotransmitter, may be more important for some functions of KCs (Iliadi et al, 2008; Knapek et al, 2013). …”
Section: Drosophila Vesicular Neurotransmitter Transportersmentioning
confidence: 99%
“…It is possible that compensatory changes in the prt mutant mitigate its effect on learning. Alternatively, the release of a peptide, rather than a classical neurotransmitter, may be more important for some functions of KCs (Iliadi et al, 2008; Knapek et al, 2013). …”
Section: Drosophila Vesicular Neurotransmitter Transportersmentioning
confidence: 99%
“…The relevance of PHM in physiology and medicine has been recently highlighted by investigations in rat brain stem that have revealed that intermittent hypoxia (associated with sleep aneas) activates PHM (Sharma et al, 2009). Also, studies on Drosophila have shown that reduced PHM activity leads to defects in memory retention and learning (Iliadi et al, 2008). In the mechanism of PHM, the two electrons required for dioxygen reduction are provided by ascorbate via one-electron reductions of the two copper centers, Cu M and Cu H .…”
Section: Introductionmentioning
confidence: 99%
“…A similar ASC-regenerating function is required in neuropeptide storage vesicles to sustain ASC-dependent amidated peptide biosynthesis. The essential role of CYB561s in this process, and its impact on neurological functions, was recently illustrated in the Drosophila mutant nemy, where decreased expression of a CYB561 homologue resulted in reduced memory retention (24). The 'electron shuttle' activity of CGCytb/CYB561A1, between ASC and membraneimpermeable ferricyanide or MDHA, was demonstrated in native chromaffin granule 'ghost' vesicles and reconstituted membrane systems (11,44) (Fig.…”
Section: Asc Recyclingmentioning
confidence: 99%